A educação do campo e o Programa Escola Ativa : uma análise do programa em escolas sergipanas - Aragão, Marcia Cristina da Cruz (2011)
The Ativa school is a government program implemented in multigrade classes rural. It was created in 1997 from the colombian experienced Escuela Nueva. Their assumptions were influenced by the movement the new school in 1920.In 2008 to meet liability claims of the movement for an educational field, the basic design was reworked as a parameter guidelines oprationals for rural school, established in 2003 and 2008 became the reference for multigrade classes in the whole country. With a goal of understand how the program is realized in pratice developed a teacher survey, research group linked to educational and social movements of the research history, society and educational thought, the nucleus of pos graduate education at the federal university of Sergipe. So We take as a method of analysis principles and procedures of a qualitative approach, the kind of case study and documentary sources as having bibliographies on the theme,the official documents of the program and observation of pratice pedagogy. We use as central categories of analysis contradiction, pedagogical work, practice, all. For that we refer to studies Trivinos 1987,Minayo 1999,Netto 2009,Frigotto 2001 and, Pistrak 1981.The study found the contradictions between pratice and theory despite the reformulation of the program incorporate the discourse of education in the field and identify the possible contradictions between the contents explored the principles of education field and a faculty pratice marked by the influence of tradicional teaching.